Qualitative and quantitative discrimination of major elements in Chitosan (natural polymer) using laser induced breakdown spectroscopy. (October 2022) - Haq, A.U.; Abrar, M.; Iqbal, T.; Khan, M.N.; Shafique, M.
Highlights: A low-cost LIBS system was used to directly obtain the spectra of chitosan a natural polymer. CF-LIBS was used to find elemental concentration of constituent elements. Elemental analysis of Hydrogen, Oxygen, Nitrogen and Carbon are detected as a major element of the sample. Hydrogen was detected as a most abundant element in the sample. Plasma temperatures was estimated by Boltzmann plot. Electron number density was estimated via FWHM of Stark broadened line fitted by Lorentzian profile on Carbon neutral line at 422.88 nm. Abstract: In this work, Laser-Induced Breakdown Spectroscopy (LIBS) is used for qualitative and quantitative analysis of Chitosan samples (natural polymer). For qualitative analysis, plasma parameters are determined, while for quantitative analysis, the initial concentration of chitosan samples is calculated. It developed a plasma plume using a second harmonic (532 nm) laser pulses, which makes the Q-Switched Nd: YAG laser compatible with delay generators and computing electronics. The component elements and their corresponding concentrations are calculated based on the strongest emission lines of the element using the line intensity ratio method and the calibration-free LIBS approach. The results obtained by both methods are compared for the effectiveness of the algorithm. In the chitosan monomer (C6 H11 NO4 )n, four major elements (hydrogen, carbon, nitrogen and oxygen) were detected and their quantities were calculated. In addition to investigating the physical behavior of plasma in the interaction of laser beams with materials, the plasma parameters (electron number density and plasma temperature) are determined by stark-broadening profile fitting and Boltzmann plot method, respectively. The results obtained show that the LIBS can be exploited for quantitative and standard analysis of industrial grade materials for better results in applications.